Chapter 42 Race, Privilege, and Relatability A Practical Guide for College and Secondary Instructors - Wells, Juliette (Taylor & Francis, 2022)
In this essay, Juliette Wells explores the expectations students bring to Austen's novels and that help to shape their interpretations as well as her own evolving perspective, informed by nearly two decades of teaching; of research on Austen in popular culture, Austen's reception, and Austen's historical readers; and of public-humanities writing and speaking on Austen and book history to a wide range of audiences. Her essay provides a practical guide for navigating the real-life challenges and opportunities for connection that arise in secondary and undergraduate classrooms once students are comfortable speaking freely about their experiences of reading Austen. She addresses two especially 'hot-button' topics: race and ethnicity, followed by socioeconomic status and offers brief overviews of contexts in history, biography, intertextuality, adaptations, and readers and fan communities, each pegged to a question or questions that students frequently ask.